Co2P Nanoparticles Wrapped in Amorphous Porous Carbon as an Efficient and Stable Catalyst for Water Oxidation - Ke, Zunjian; Wang, Haojie; He, Dong; Song, Xianyin; Tang, Chongyang; Liu, Jiangchao; He, Lanli; Xiao, Xiangheng; Jiang, Changzhong (Frontiers in Chemistry, 2018)
Exploring highly active, enduringly stable, and low-cost oxygen evolution reaction catalysts continues to be a dominant challenge to commercialize renewable electrochemical water-splitting technology. High-active and earth-abundant cobalt phosphides are recently considered as promising candidates. However, the poor inherent electron transfer efficiency and instability hinder its further development. In this work, a novel approach was demonstrated to effectively synthesize Co2P nanoparticles wrapped in amorphous porous carbon framework (Co2P/C). Benefiting from extremely high specific surface area of porous carbon, plenty of active sites were adequately exposed. Meanwhile, unique anchoring structure between Co2P nanoparticles and amorphous carbon outerwear insured high transfer efficiency and superior stability of Co2P/C. Due to these favorable properties, low overpotential of 281 mV at 10 mA cm-2 and Tafel slope of 69 mV dec-1 were achieved in resultant Co2P/C catalyst. More significantly, it only exhibited a negligible overpotential increase after 30 hours stability test, and these performance entirely preceded commercial RuO2 benchmark. In summary, we proposed a simple and feasible strategy to prepare metal phosphides wrapped with amorphous porous carbon outerwear for efficient and durable electrochemical water oxidation.